Exploring Public Sentiments Using Big Data on Superhub Spatial Development of Nusantara, the New Capital City of Indonesia - Ibnu Syabri; Ridwan Sutriadi; Nugraha Ramadhany (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
Superhub development is crucial for enhancing the economic prowess and sustainability of a region, focusing on bolstering its global competitiveness and amplifying its impact on national and regional growth. In the case of Nusantara, Indonesia’s new capital city, understanding public sentiment towards its development plan is essential. This study employed sentiment analysis, combining a comprehensive dataset of 433,637 tweets from 2020 with public documents and machine-learning tools to accurately gauge public opinion. Six key components of regional development emerged from the analysis, reflecting public discourse on IKN’s planning and execution. Geographically, sentiment across the 33 provinces was evenly distributed, with 63% positive, 24% negative, and 13% neutral sentiments observed in the tweets. However, sentiment fluctuated throughout the year, with a surge in negative sentiment early in 2020 due to concerns over financing risks and economic challenges. Nonetheless, negativity waned as the year progressed, with positive tweets steadily increasing from April to December. These findings offer valuable insights for guiding the development of Nusantara, aiding policymakers in addressing public concerns, and ensuring a more informed and inclusive approach. Such sentiment analysis proves instrumental in shaping the strategic trajectory of the new capital city, fostering sustainable growth and public support.